Τhe legitimation of anticommunist political discourse in Greece during the crisis - Boukala, Salomi (The Greek Review of Social Research, 2023)
Drawing upon the framework of Discourse Historical Approach to Critical Discourse Analysis and combining it with the argumentative perspective of the Aristotelian tradition, this article attempts to show how the banality of anticommunism dominated the Greek political scene in a period that extends from Venizelos’ Idionymon and especially to the recent economic and political crisis. Based on the theoretical frames of legitimation and totalitarianism, my aim is to explain how anti-communist discourse escalates in times of crisis and is extended beyond the limits of far right rhetoric, while being legitimized on the basis of the ‘communist threat’ archetype.